2009
DOI: 10.1172/jci38918
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating cholecystokinin-2 receptor inhibits progastrin-dependent colonic crypt fission, proliferation, and colorectal cancer in mice

Abstract: Hyperproliferation of the colonic epithelium, leading to expansion of colonic crypt progenitors, is a recognized risk factor for colorectal cancer. Overexpression of progastrin, a nonamidated and incompletely processed product of the gastrin gene, has been shown to induce colonic hyperproliferation and promote colorectal cancer in mice, but the mechanism of pathogenesis has not been defined. Cholecystokinin-2 receptor (CCK2R) is the primary receptor for cholecystokinin (CCK) and amidated gastrin. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 71 publications
6
81
2
Order By: Relevance
“…S1M and S1N) when compared with controls. In addition, convincing data from Jin and colleagues suggested that progastrin can act at least partly in vivo via activation of CCK2 receptors (16). Yet, we were not able to detect CCK2 receptor mRNA in the colorectal cancer cells used to characterize the effects of progastrin in this study (data not shown), suggesting that progastrin may display both direct and indirect effects and/or that the progastrin signaling networks in mice and human are somewhat different.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…S1M and S1N) when compared with controls. In addition, convincing data from Jin and colleagues suggested that progastrin can act at least partly in vivo via activation of CCK2 receptors (16). Yet, we were not able to detect CCK2 receptor mRNA in the colorectal cancer cells used to characterize the effects of progastrin in this study (data not shown), suggesting that progastrin may display both direct and indirect effects and/or that the progastrin signaling networks in mice and human are somewhat different.…”
Section: Discussioncontrasting
confidence: 53%
“…We previously demonstrated that progastrin regulates the Wnt and Notch pathways in colorectal cancer (12,14), suggesting that it could affect the phenotype of colon CSCs, which rely on these pathways for their survival (15). Progastrin was shown to promote the proliferation of progenitor cells in the mouse colonic epithelium (16) and a link has been suggested between progastrin expression and populations of cells expressing CD133 (17), DCAMKL1 (18), or CD44 (19) in mouse colonic crypts and human cancer cell lines. Yet, expression of these markers is not restricted to CSCs (20)(21)(22)(23), and the functional role of progastrin on CSC self-renewal and tumor-initiating potential has not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Separated serum was stored in Ϫ80°C until usage. Amidated gastrin levels were measured with antiserum 1296 as previously described (8,15).…”
Section: Evaluation Of H Felis Colonization By Quantitative Real-timmentioning
confidence: 99%
“…The antiapoptotic effect of gastrin might be associated with CCK-2 signaling activity. It has been reported that CCK-2 pathway could enhance cell proliferation in intestinal epithelium, 25 which could counteract apoptotic pathway such as Bax expression.…”
Section: Discussionmentioning
confidence: 99%